PENGARUH TINGKAT INTENSIFIKASI TERHADAP PRODUKTIVITAS TEBU PETANI BINAAN PABRIK GULA (PG) GONDANG BARU KABUPATEN KLATEN PROVINSI JAWA TENGAH DALAM UPAYA PENCAPAIAN SWASEMBADA GULA - Ferhat, Amalia; Vandrias, Dewantoro; Hamidah, Siti (Jurnal Dinamika Sosial Ekonomi, 2015)
The research purposes of this study was : (1) Analyze the level of tntensification to performed on each shoot. (2) Analyze the determine the level of intensification about the production of sugar cane. (3) Find out what are the obstaclesand how to overcome these problems. The research carried out using a survey method. The analitical method used the method of linier regression analysis. Intake of respondents using purposive sampling with 75 people, who contribute the maximum to the sugar mill with the diffrent buds condition. The results showed level of intensification in the first shoots were in both shoots and the third and fourth in the high and low categories. The influence on the productivity level of intensification shows the first buds will productivity of 36, 615 qu/he without the influence of the intensification. The productivity of the second shoots as much as 91,324 qu/he and 11.934,684 qu/he without the influence of the intensification. The third and fourth shoots will be descreased by of variabledegreeKey words :Intensification, sugar cane , productivity, ratoon cane